2023
DOI: 10.1007/s10526-023-10207-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of multiple defense responses in wheat plants against stripe rust using mycorrhizal fungi and Streptomyces viridosporus HH1

Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici, is one of the most devastating diseases of wheat worldwide. This study dealt with investigating the biocontrol activity of mycorrhizal colonization and/or application of Streptomyces viridosporus HH1 against stripe rust of wheat. In vitro, data showed that S. viridosporus HH1 had a strong anti-spore germination effect on uredospores of P. striiformis (90% reduction). A 84.2% reduction in the disease severity was achieved in the infected wheat plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Disease severity may also be reduced by AMF colonization of eggplants infected by R. solani, which triggers host defense responses in plants under stress caused by plant pathogens (Rashad et al 2020b). AMF can also enhance plant resistance, by promoting plant growth and vigor via improvement of plant nutrition (El-Sharkawy et al, 2023) and production of plant hormones (Song et al, 2020). In the present study, co-inoculation of infected plants with the two biocontrol agents decreased disease severity by 26%, indicating an additive action of the N. circulans YRNF1 and AMF.…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity may also be reduced by AMF colonization of eggplants infected by R. solani, which triggers host defense responses in plants under stress caused by plant pathogens (Rashad et al 2020b). AMF can also enhance plant resistance, by promoting plant growth and vigor via improvement of plant nutrition (El-Sharkawy et al, 2023) and production of plant hormones (Song et al, 2020). In the present study, co-inoculation of infected plants with the two biocontrol agents decreased disease severity by 26%, indicating an additive action of the N. circulans YRNF1 and AMF.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the induction of different defense mechanisms in the plant due to the occurrence of various biocontrol agents. Moreover, some Streptomyces and Trichoderma species produce secondary metabolites, directly inhibiting the activity of GST enzymes in the plant [45][46][47]. These metabolites encompass various classes, categorized as follows: (a) compounds involved in regulatory activities, which encompass growth factors, morpho-genic agents, siderophores, and agents promoting plant-rhizobia interaction; (b) antagonistic agents, consisting of those with antiprotozoan, antibacterial, antifungal, and antiviral effects; (c) agrobiological agents, including insecticides, pesticides, and herbicides; and (d) pharmacological agents, which comprise neurological agents, immunomodulators, those with antitumoral effects, and enzyme inhibitors [48].…”
Section: Discussionmentioning
confidence: 99%
“…SA is recognized for activating responses against biotrophic pathogens, while plant responses to necrotrophic pathogens are predominatly governed by the JA and ET pathways [ 152 ]. In a study conducted by El-Sharkawy et al [ 156 ], molecular investigation revealed that mycorrhizal colonization with an AMF inoculum containing three types of AMF ( R. irregularis , R. clarum , and G. gigantean ) up-regulated the defensive gene ethylene response factor protein 3 ( JERF3 ) in wheat plants infected by Puccinia striiformis f. sp, the causal agent of stripe rust. Furthermore, two SA-related genes encoding carboxyl methyltransferases, Os11g0260100 and Os01g0701700 , were up-regulated in the leaves of cultivated rice infected by M. oryzae after inoculation with R. intraradices [ 91 ].…”
Section: Molecular Strategies Contributing To Cereal and Oilseed Tole...mentioning
confidence: 99%